2018
DOI: 10.1007/s12119-018-9549-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sexism and Rape Myths on Victim Blame

Abstract: Rape myths are false beliefs about sexual violence that encourage blaming the victim and exonerating the offender. Within the framework of the Ambivalent Sexism Theory, we tested a model investigating the effect of each dimension of ambivalent sexism on the endorsement of each rape myth, and in turn the effect of each myth on the attribution of responsibility (to the perpetrator versus to the victim) in case of sexual violence. Participants were 264 students (54.9% females). Results showed that hostile sexism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 31 publications
8
47
0
1
Order By: Relevance
“…Some studies have found that higher levels of HS were associated with greater acceptance of domestic violence perpetrated by men (Sakall, 2001) and greater offender's justification in case of rape (Rollero & Tartaglia, 2018). Thus, HS seems to be a potent enforcer of traditional power relations between genders and a strong predictor of acceptance of violence against women, for both adult and young adult population.…”
Section: Recognising Violence: the Role Of Ambivalent Sexism And Socimentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have found that higher levels of HS were associated with greater acceptance of domestic violence perpetrated by men (Sakall, 2001) and greater offender's justification in case of rape (Rollero & Tartaglia, 2018). Thus, HS seems to be a potent enforcer of traditional power relations between genders and a strong predictor of acceptance of violence against women, for both adult and young adult population.…”
Section: Recognising Violence: the Role Of Ambivalent Sexism And Socimentioning
confidence: 99%
“…On the one hand some authors found that individuals who presented higher levels of BS were more likely to blame victims of rapes (Abrams, Viki, Masser, & Bohner, 2003;Durán, Moya, Megías, & Viki, 2010). On the other hand, recent research on young adults' violence and rape myths acceptance found no significant effect of BS (Rollero & Tartaglia, 2018).…”
Section: Recognising Violence: the Role Of Ambivalent Sexism And Socimentioning
confidence: 99%
See 2 more Smart Citations
“…If this is the case, we might expect that an increase in sexism could then relate to other outcomes such as decreased empathy for victims, particularly female victims of rape. It is argued that sexist individuals may be more inclined to adopt rape myths, such as that women often say “no” but mean “yes,” or deserve to be raped if they dress provocatively (Rollero & Tartaglia, ). Thus, a sexist attitude may include placing greater responsibility for rape on the female victims of rape.…”
Section: Introductionmentioning
confidence: 99%